Legal Analysis of Banking Crimes and Money Laundering in Indonesia - Abd. Rahman Alwi Pase; David Nwanna Dumbiri (Program Pascasarjana UIN Sumatera Utara Medan, 2024)
The rapid development of the banking sector and information technology in Indonesia has significantly facilitated financial transactions while simultaneously increasing the risk of banking crimes and money laundering activities. Banking crimes such as fraud, embezzlement, abuse of authority, and financial transaction manipulation frequently serve as predicate offenses for money laundering. This study aims to analyze the legal framework governing banking crimes and money laundering in Indonesia, examine their interrelationship, and identify challenges in their prevention and enforcement. This research employs a normative legal method using statutory and conceptual approaches. Data were collected through a literature review of primary, secondary, and tertiary legal materials and analyzed qualitatively. The findings indicate that banking crimes are closely linked to money laundering, as offenders often exploit banking systems to conceal the illicit origins of criminal proceeds through complex financial transactions, including layering, the use of third-party accounts, and cross-border fund transfers. Although Indonesia has established a comprehensive legal framework to combat these crimes, law enforcement efforts continue to face challenges, including weak supervision, limited technical capacity of law enforcement agencies, inadequate inter-agency coordination, and the increasing sophistication of technology-based criminal methods. The study further reveals that current measures remain predominantly repressive, while preventive strategies have not been optimally implemented. Therefore, strengthening regulatory frameworks, enhancing institutional cooperation, improving human resource capabilities, and adopting advanced technological monitoring systems are essential to effectively prevent and combat banking crimes and money laundering in Indonesia.